Akun TikTok (@kampungarabalazhar) Sebagai Media Belajar Bahasa Arab Online - Amzaludin, Amzaludin; Ain, Indhun Qurottul; Khumairah, Eka Silfia (Universitas Nusantara PGRI Kediri, 2023)
This study aims to describe video-based online Arabic learning media and how the role, benefits and disadvantages of video as a medium in language learning, while video as a learning medium in this study is content from a tiktok account with a username @kampungarabalazhar. The research method in this paper uses is qualitative with a descriptive approach and the research process through library research. There are several terms used in the media among them are al-Wasa’il al-Idhah or al-Wasa’il al-Taudhihiyyah, wasa’il al-Ta’lim, al-Wasa’il al-Ta’limiyah and there are also those who use the term al-Mu’ayyanaat al-Sam’iyah wa al-Bashariyah. Although the terms used are different, but all of them lead to the same understanding, namely learning media, that audio-visual media is a modern instructional media in accordance with the times (advances in science and technology) which includes media that can be seen, heard and seen, Film or Video is one type of audio-visual media. The TikTok application will be an interesting and fun learning medium if processed and used properly. Through the TikTok application, an educator can create interactive learning in accordance with the situation and conditions of students and able to adapt to the times.